Applying the Health Belief Model to Examine Obesity Prevention Behaviors Among Female Adolescents in Sukoharjo, Central Java, Indonesia - Nurjihan Luthfia Nabilla; Eti Poncorini Pamungkasari; Argyo Demartoto; Bhisma Murti; Cynthia Permata Sari (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Obesity is a growing global health problem, especially among adolescent girls. The increasing prevalence of obesity in Indonesia, including in Sukoharjo Regency, is a serious concern because obesity contributes to various non-communicable diseases. This study aims to analyze the influence of the Health Belief Model (HBM) application on obesity prevention behavior among female adolescents at PPTQ Al Rasyid Kartasura, Sukoharjo, Central Java. Subjects and Method: This study used a cross-sectional Study design. The study was carried out from February to March 2025 at PPTQ Al Rasyid Junior and Senior High School Kartasura, Suko¬harjo. The study sample was 210 students who were selected by an exhaustive sampling technique. The data collection instrument was in the form of a structured questionnaire that measured the HBM constructs, namely perceived susceptibility, perceived severity, perceived benefit, perceived barriers, cues to action, and self-efficacy. Data analysis was conducted using multiple linear regression. The dependent variable was obesity prevention behavior. Results: Obesity prevention behaviors increased with high perceived susceptibility (b= 0.17; 95% CI= 0.01 to 0.34; p= 0.022), perceived severity (b= 0.17; 95% CI= 0.01 to 0.34; p = 0.022), perceived benefits (b= 0.31; 95% CI= 0.03 to 0.59; p= 0.028), cues to action (b= 0.25; 95% CI= 0.02 to 0.49; p= 0.033), self-efficacy (b = 0.19; 95% CI= 0.01 to 0.37; p= 0.045), and decreased with the high perceived barriers (b = -0.18; 95% CI= -0.35 to -0.01; p= 0.046). Conclusion: High perceived susceptibility, perceived severity, perceived benefit, cues to action, and self-efficacy, as well as low perceived barriers, contribute to improving obesity prevention behaviors among female adolescents.